A taxonomic revision and systematics study of Prunus L. (s.l.) in continental Southeast Asia - Rueangruea, Sukid (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2024)
This thesis aims to provide a complete account of the genus Prunus L. for Thailand, Myanmar, Laos, Cambodia, and Vietnam. In addition, the relevant specific problems of Prunus in Southeast Asia are outlined, and the generic relationships between Asian members are assessed using a molecular approach. A taxonomic history of the genus and history of botanical works relevant to the genus Prunus in continental Southeast Asia and neighboring regions are given. The economic and ethnobotanical significance of some members is also provided. General morphological characteristics are described in terms specific to the study group and explained, and when appropriate, some figures are provided to add explanation. Molecular phylogenetic analysis was undertaken with nuclear and plastid DNA gene regions (ETS-RosF and IGS6R; psbA-trnH, rpl16, rps16, and trnC-petN). The nuclear dataset analysis, ETS-RosF, and IGS6R confirmed some patterns of infrageneric classification. In addition, the plastid dataset analyses, psbA-trnH, rpl16, rps16, and trnC-petN, did not provide well-resolved or supported trees from their analysis. A combined analysis of nuclear and plastid genes provided improved resolution and support, and the findings concerning the infrageneric classification of Prunus and the utility of the markers for DNA barcoding are discussed. Mesopygeum formed a monophyletic group in all analyses, but section Laurocerasus was not supported as it is currently defined and was generally paraphyletic. Many well-supported subgroupings were identified. The main part of this thesis's taxonomic chapter aimed to provide a complete revision of the genus Prunus in continental Southeast Asia. The revision was undertaken at the Herbarium, Department of Botany, Trinity College Dublin (TCD) and at the Herbarium, Royal Botanic Gardens, Kew (K). The major herbaria in Europe, BM, E, K, L, P, and TCD together with regional herbaria in Asia; Thailand, BKF, BK, CMUB, QBG; Cambodia; Japan, KYO and FU; Laos, FOF; Myanmar, RAF; and Vietnam, VNM which have good collections of South East Asian were visited to study their collections, including types: ten field trips, totaling six months were made to Laos, Myanmar, Thailand, and Vietnam in 2019 and 2020. The species were also reviewed and described to clarify their nomenclatural status, geographic distributions, and diagnostic character states. Full descriptions of genera and species, keys, synonyms, distribution maps, photographs, information about distribution, ecology, vernacular names, and specimens examined are given. In chapter 5, information about habitats, ecology, distributions, and endemism of Prunus are provided with particular emphasis on continental Southeast Asia taxa. The Prunus species in continental Southeast Asia are found in various habitats except Mangrove, Swamp, and Beach forests. They are usually common in dry land, shade, and open habitats. The first group comprises the northern species, the Indo-Burmese, and the Sino-Himalayan elements. The second group contains some widespread taxa, but most belong to the Indo-Chinese element and are mostly confined to the central and upper Indo-Chinese peninsula. Prunus did not appear as monophyletic using the nuclear dataset analysis, ETS-RosF, and IGS6R. In addition, the plastid dataset analyses, psbA-trnH, rpl16, rps16, and trnC-petN, could have provided better-resolved and supported trees individually. 236 synonyms are recognized from the 50 Prunus recognized in continental Southeast Asia, including 26 names that are lectotypified here and 29 new synonyms. Four species (8 %) are new records to Thailand: P. kalkmanii, P. polystachya, P. pygeoides, and P. ridleyi. This updates biogeographic knowledge of the region and reflects the need to explore the region's diversity further. There is also no doubt that many species still need to be described because many specimens do not match any known species among the existing collections. This Ph.D. has therefore reviewed the genus Prunus in continental Southeast Asia, mainly based on morphological analysis of all available Prunus specimens, and provided a basis for the future completion of accounts of the Rosaceae for the Flora of Thailand Project. In addition, Prunus's historical biogeography, evolution, and phylogeny of Prunus were considered. The detailed revision of Prunus from continental Southeast Asia provides the taxonomic framework for conserving and utilizing its regional genetic resources. Many species of Prunus in continental Southeast Asia have been exposed to critical over-exploration in their natural habitats for ornamental or medicinal purposes and thus require strict protection for sustainable development. Herein, a preliminary assessment of their conservation status has been made.
APPROVED
Keywords: characters; cherry blossom; classification; conservation; continental Southeast Asia; phylogenetics; Prunus; Rosaceae; taxonomy.